A passive seismic approach to estimating the thickness of sedimentary cover on the Nullarbor Plain, Western Australia. Issue 5 (3rd July 2016) - Scheib, A.; Morris, P.; Murdie, R.; Delle Piane, C.
ABSTRACT: Passive seismic approaches, using a single-station, enable rapid, cost-effective and non-invasive estimates of the thickness of sedimentary rocks overlying crystalline basement. This approach was applied to estimate the Cenozoic and Cretaceous succession beneath the Nullarbor Plain in southeastern Western Australia. Passive seismic data acquired at the majority of the 94 sites show a single, strong resonance frequency peak between 0.4 and 0.6 Hz suggesting an impedance contrast of a single subsurface layer. Modelling these resonance frequencies against known stratigraphy at 12 drill holes shows that this impedance contrast corresponds to the contact of the base of the Cenozoic–Cretaceous sedimentary succession of the Eucla and Bight basins with the crystalline basement. Data from the remaining sites produced sediment thickness estimates ranging from only tens of metres near the western edge of the Nullarbor Plain to over 860 m near its southern margin. Near this margin, rapid thickening of the sedimentary cover is coincident with an interpreted paleosea-cliff or indicative of localised faulting. Beneath the Western Australian portion of the Nullarbor Plain the sedimentary cover is on average 320 m thick with the succession thinning gradually towards the margins of the basin. A passive seismic approach is thus seen as a useful screening tool for the mineral exploration industry in areas that are under cover allowing for better targeting and cost-reduction in greenfields exploration.